Results 1 to 2 of 2

Math Help - Given (p ⇒ q) and (r ⇒ s), use Fitch to prove (p ∨ r ⇒ q ∨ s )

  1. #1
    Newbie
    Joined
    Apr 2013
    From
    Belgrade
    Posts
    5

    Given (p ⇒ q) and (r ⇒ s), use Fitch to prove (p ∨ r ⇒ q ∨ s )

    Given (pq) and (rs), use the Fitch System to prove (prqs)

    p => q - premise
    r => s - premise

    Goal : p | r => q | s
    Follow Math Help Forum on Facebook and Google+

  2. #2
    Member
    Joined
    Sep 2009
    From
    Minnesota
    Posts
    80
    Thanks
    8

    Re: Given (p ⇒ q) and (r ⇒ s), use Fitch to prove (p ∨ r ⇒ q ∨ s )

    Use the fact that p \rightarrow q is logically equivalent to ~p ∨ q.
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Explaining why x ≥ 4 ⇒ x > 4 is false
    Posted in the Discrete Math Forum
    Replies: 7
    Last Post: August 29th 2012, 07:11 PM
  2. Replies: 9
    Last Post: December 10th 2011, 02:23 PM
  3. Prove that (p ⇒ q) ⇔ (q ⇒ p)
    Posted in the Discrete Math Forum
    Replies: 7
    Last Post: February 14th 2011, 11:35 AM
  4. Replies: 0
    Last Post: June 28th 2010, 09:32 PM
  5. A ⊂ b ⇒ p (a) ≤ p (b)
    Posted in the Advanced Statistics Forum
    Replies: 7
    Last Post: February 16th 2010, 02:18 PM

Search Tags


/mathhelpforum @mathhelpforum